Hemopexin as an Inhibitor of Hemolysis-Induced Complement Activation - Poillerat, Victoria; Gentinetta, Thomas; Leon, Juliette; Wassmer, Andreas; Edler, Monika; Torset, Carine; Luo, Dandan; Tuffin, Gerald; Roumenina, Lubka T. (Frontiers in Immunology, 2020)
Hemopexin is the main plasmatic scavenger of cell-free heme, released in the context of intravascular hemolysis or major cell injury. Heme is indispensable for the oxygen transport by hemoglobin but when released outside of the erythrocytes it becomes a danger-associated molecular pattern, contributing to tissue injury. One of the mechanisms of pro-inflammatory action of heme is to activate the innate immune complement cascade. Therefore, we hypothesized that injection of hemopexin will prevent hemolysis-induced complement activation. Human plasma-derived hemopexin is compatible with the heme clearance machinery of the mice. 100 or 500 mg/kg of hemopexin was injected in C57Bl/6 mice before treatment with phenylhydrazine (inducer of erythrocytes lysis) or with PBS as a control. Blood was taken at different timepoints to determine the pharmacokinetic of injected hemopexin in presence and absence of hemolysis. Complement activation was determined in plasma, by the C3 cleavage (western blot) and in the kidneys (immunofluorescence). Kidney injury was evaluated by urea and creatinine in plasma and renal NGAL and HO-1 gene expression were measured. The pharmacokinetic properties of hemopexin (mass spectrometry) in the hemolytic mice were affected by the target-mediated drug disposition phenomenon due to the high affinity of binding of hemopexin to heme. Hemolysis induced complement overactivation and signs of mild renal dysfunction at 6h, which were prevented by hemopexin, except for the NGAL upregulation. The heme-degrading capacity of the kidney, measured by the HO-1 expression, was not affected by the treatment. These results encourage further studies of hemopexin as a therapeutic agent in models of diseases with heme overload.